Ao internacional e além: as relações de poder-saber na constituição da identidade transnacional brasileira inscritas em livros didáticos de Português para estrangeiros - Cardoso, Jorcemara Matos (2021)
Over the decades, numerous events were inaugurated in the Brazilian diplomacy device (BDD). A whole semiotic was built on top of it, which started organizing how people see and talk about Brazil abroad and within the country itself. However, from the beginning of the 1990s onwards, the ideals of the New Republic designed in the 1988 Brazilian constitution started to go through the construction of policies and institutions that bring to the public debate problematic issues intensely debated by civil society movements. On the sidelines of official state discourses for centuries. This progressive turn has started to cross and foster, in many ways, the configuration of various objects, such as textbooks (TB). As part of the weaving of the Brazilian diplomacy device, the books carry not only the knowledge of promoting the teaching but the remnants of a network of practices (discursive and non-discursive) that activate trans-Brazilianity archives, to sustain, in a given historical period, the emergence of the Brazilian transnational identity (BTI). This research sought to study the relation of power and knowledge that inscribe the Brazilian transnational identity in the BDD, based on these networks of practices established in Portuguese textbooks for foreigners, produced and published by the Rede Brasil Cultural sectors and Brazilian Embassies. In order to verify both the identity manufactured in these textbooks and the mechanics and engineering, which in turn guarantee their conditions of existence. To shed light on those issues, we start from Discourse Analysis of frontiers, of historical and enunciative basis by invoking concepts such as the power-knowledge (FOUCAULT, 1984; 2005; 2008; [1981] 2018; DELEUZE, 1990; DELEUZE e GUATARRI, 1997; AGAMBEN, 2005; GREGOLIN, 2016), medium, scenes of enunciation (MAINGUENEAU 2004; 2006; 2008b; 2013; 2016; DEBRAY 1995, 1997, 2004), among other tools used during the analysis. In parallel, we held important dialogues with authors from different fields who forge their writings as resistance to certain configurations of (trans)national identity (FANON, 1968; GUATARRI e RONILK, 1996; BHABHA, 1998; HALL, 2005; BAUMAN, 2005; WALSH; 1994, 2019) and certain epistemic knowledge that supports, even today, a colonizing and segregating vision of (trans) Brazilianness (NASCIMENTO, 1978; GONÇALEZ and HASSENBELG, 1982; ORTIZ, 1986; 2013; SOUZA, 2000; 2009; 2017). The discussions and analyses show us the activation of language and culture as founding variables of transnational identity, however, promoted by a fragmented and disjointed foreign policy. Such fragmentation allows many speeches and different individuals to operate meanings in the textbook, allowing them to slide from a language book to an (inter)culture book, or even a symbol book of government (and not State) policies of government (and not State) policies dissemination and promotion of Brazil's image abroad. Concerning the activated imaginary that constitute the BTI and individuals transnationals, we noted three central points: the first one reinforces discourses hegemonic of a romanticized Brazil and racial paradise; the second one constitutes the ambivalence of activating a Brazil is progressive, plural, socially based, defender of the democratic rule of law and, at the same time, resignify mummified rags of the colonizing discourse (FANON, 1968); the third one, crossed by the first two, encourage reflection and engagement on the images of a Brazil of dialogue and conflict. This last one, permeated by a pedagogy of dialogue (GADOTTI; FREIRE; GUIMARÃES, 1994), criticizes the State through its official channels. Among other processes of regularities and ruptures, there is the distension of the senses of "foreigners" (called to belong to the nation) and the near invisibility of entire sectors of Brazilian society. Finally, we realized that, even in periods with high democratic values, in which the forging of voices peripheralized in State institutions, they provoke advances in the ways of making Brazil see and enunciate (inside and outside of its borders). The secular practices of segregation, exclusion, and genocide, operated by the discourses hegemonic, still cross, under different degrees, how the image of the (trans)national is constituted in the TBs – which often appears rooted in the vision of a white, masculine, hetero-normative, of a privileged class. This power mechanics prove to be even more dangerous when the democratic values lose space for the practice of a policy that sees in social bodies a frontier to say who is or not a citizen of the nation.